Psychological Basis for The Use of Digital Technologies In the Preparation of Future Physical Education Teachers (Journal of Pedagogical Inventions and Practices, 2023)
This article describes the psychological basis for the use of digital technologies in the training of future physical education teachers. The types of psychological foundations and their direct impact on human activity are identified, in addition, the stages of the formation of protective mechanisms for future teaching staff, the useful and negative foundations of these components. The article examines and analyzes studies conducted by influential psychologists Z. Freud and Higgins. Psychological foundations according to Freud's theory, the significance of the concept of Higgins' mechanisms and foundations in the training of future teachers of physical education is stated